The Addition of ViriditecTM Aqueous Ozone to Peracetic Acid as an Antimicrobial Spray Increases Air Quality While Maintaining Salmonella Typhimurium, Non-pathogenic Escherichia coli, and Campylobacter jejuni Reduction on Whole Carcasses - Dittoe, Dana Kristen; Feye, Kristina Marie; Peyton, Bob; Worlie, Drew; Draper, Michael J.; Ricke, Steven C. (Frontiers in Microbiology, 2019)
Currently, the most utilized antimicrobial in processing facilities is peracetic acid, PAA; however, this chemical is increasingly recognized as a hazard to human health. Preliminary evidence suggests that ozone, when introduced in a specific manner, can reduce the noxious nature of PAA. Therefore, the objective of the current study was to evaluate the efficacy of TetraClean Systems aqueous ozone, O3, in combination with PAA as an antimicrobial spray on whole chicken carcasses. This trial used 70 whole hen carcasses (7 treatments; 10 replications) that were inoculated in a 400 mL cocktail containing Salmonella, Escherichia coli, and Campylobacter (107 CFU/mL) and allowed to adhere for 60 min at 4°C for a final concentration of 105 to 106 CFU/g. The experimental 5 s (4×) spray treatments included: a no treatment negative control, TW; TW + O3 (10 ppm), TW + PAA (50 ppm), TW + PAA (500 ppm), TW + O3 + PAA (50 ppm), and TW + O3 + PAA (500 ppm). During treatment application, ambient PAA vapor was measured with a ChemDAQ Safecide PAA vapor sensor. After treatment, carcasses were immediately rinsed in 400 mL of nBPW for 2 min. Following rinsing, the dot method was utilizing for enumeration with 10 μL of rinsate being serially diluted, plated on XLD and mCCDA agar, and incubated aerobically at 37°C for 24 h or microaerophilically at 42°C for 48 h. Log-transformed counts were analyzed using ANOVA in JMP 14.0. Means were separated using Tukey’s HSD when P ≤ 0.05. There was a significant treatment effect among Salmonella, E. coli, and Campylobacter counts, and a significant treatment effect among ambient PAA (P < 0.05). TW + O3 + PAA (500 ppm), reduced Salmonella significantly compared to TW (5.71 and 6.30 log CFU/g). Furthermore, TW + PAA (500 ppm), reduced the presence of E. coli significantly compared to TW or no treated control (5.57 and 6.18 log CFU/g). Also, TW + PAA (50 ppm), TW + PAA (500 ppm), and TW + O3 + PAA (500 ppm) significantly reduced Campylobacter compared to carcasses not treated (4.80, 4.81, and 4.86 log CFU/g). Lastly, the addition of ozone significantly reduced the ambient PAA when O3 was added to 500 ppm of PAA, as TW + O3 + PAA (500 ppm) produced less ambient PAA than TW + PAA (500 ppm) (0.052 and 0.565 ppm). In conclusion, the addition of ozone to PAA may demonstrated the ability to effectively reduce ambient PAA, thus increasing employee safety.